(untitled) (ModaPalavra e-periódico, 2025)
The field of disability studies, which starts from the perspective of people with disabilities themselves to debate their social inclusion, has recently recognized the importance of intersectionality in the construction of the subjectivity of people with disabilities. Thereby, based on the assumption that considering the intersectionality and subjectivity of people with disabilities is fundamental to promoting full social inclusion, this article aims to investigate how the subjectivity and intersectionality of people with disabilities have been addressed in Brazilian publications about inclusive fashion. Based on an integrative literature review, conducted in Brazilian fashion and design journals, this article investigates aspects used to analyze and describe the public of people with disabilities and how practical and aesthetic-symbolic functions are balanced in research on inclusive fashion. It appears that, in the Brazilian scenario, the majority of scientific production on inclusive fashion delimits its audience based on the marker of disability, emphasizing practical functions related to accessibility, without considering the intersectionality and subjectivity of people with disabilities. Some articles, however, present considerations associated with the use of fashion to promote the self-esteem of people with disabilities, reinforcing the need to broadly understand this public and to consider the aesthetic-symbolic functions to promote full social inclusion within the scope of fashion.